2016
DOI: 10.1007/s10896-016-9854-7
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Intimate Partner Violence and Traumatic Brain Injury: A Call for Interdisciplinary Research

Abstract: An emerging body of research suggests that survivors of intimate partner violence (IPV) are at a high risk for sustaining traumatic brain injury (TBI). However, most scholars and practitioners working on the problem of IPV have not examined how TBI could be related to their familiar subject of study. Concomitantly, little work in the brain injury field has been done to examine TBI in the context of IPV. In this paper, we encourage cross-collaboration among these fields.To that end, we consider the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 45 publications
0
38
1
1
Order By: Relevance
“…Furthermore, the goal of the working group is to examine the effect IPV-related head trauma has on the neural, psychological, and cognitive outcomes of these injuries to identify targets for interventions. However, as Hunnicutt and colleagues highlighted in their recent call for research on this topic, there is a risk that increased attention to the prevalence and sequelae of head trauma in this population could lead to additional stigmatization and discrimination against this already vulnerable population (Hunnicutt, Lundgren, Murray, & Olson, 2017). As such, we want to ensure that all investigators reporting results of research from the working group do so in a sensitive way that does not increase stigma, but instead highlights how understanding the effects of IPVrelated head trauma can be used to increase the accessibility of resources and to adjust methods of rehabilitation and intervention to help improve the ability to work, engage in psychotherapy, navigate the legal system, and engage in safety planning in individuals who have experienced IPV.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the goal of the working group is to examine the effect IPV-related head trauma has on the neural, psychological, and cognitive outcomes of these injuries to identify targets for interventions. However, as Hunnicutt and colleagues highlighted in their recent call for research on this topic, there is a risk that increased attention to the prevalence and sequelae of head trauma in this population could lead to additional stigmatization and discrimination against this already vulnerable population (Hunnicutt, Lundgren, Murray, & Olson, 2017). As such, we want to ensure that all investigators reporting results of research from the working group do so in a sensitive way that does not increase stigma, but instead highlights how understanding the effects of IPVrelated head trauma can be used to increase the accessibility of resources and to adjust methods of rehabilitation and intervention to help improve the ability to work, engage in psychotherapy, navigate the legal system, and engage in safety planning in individuals who have experienced IPV.…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados obtenidos son además congruentes con diversos estudios que ponen de manifiesto la elevada prevalencia de traumatismos craneoencefálicos (Hunnicutt et al, 2017;Wong et al, 2014) Además del TEPT, la depresión y ansiedad son de las repercusiones psicológicas más destacadas por numerosos autores (Pico-Alfonso et al, 2004;Strigo et al, 2010, Torres y Pérez, 2014, las cuales podrían verse exacerbadas por la toma de conciencia de los déficits neuropsicológicos y de los problemas relacionados con éstos, ya que ello podría conducir a una disminución en la percepción de competencia por parte de estas mujeres. Por otro lado, consideramos que las distorsiones cognitivas que se han señalado en diversos estudios (Dutton et al, 1994;Heim, Trujillo Tapia y Quintanilla Gonzáles, 2018) podrían estar relacionadas con los déficits en las funciones ejecutivas como el razonamiento y capacidad de cambio de criterio, ya que dificultarían la generación de pensamientos alternativos y conclusiones no distorsionadas.…”
Section: Discusión Y Conclusionesunclassified
“…2–5 However, it is increasingly recognized brain injury (BI) resulting from violent blows to the head, face, and neck, and/or strangulation, is also a common part of this experience. 6,7 Even though some survivors may experience neuropsychological impairment without BI 8 , a recent review 9 reported up to 92% of women reported symptoms consistent with BI following an IPV incident – including headaches, memory loss, difficulty thinking, paying attention, or getting organized. 4,10 Thus, it is clear that IPV may result in a multitude of physical, psychological, and social consequences, however, the extent to which BI plays a role in such dysfunction is unknown.…”
Section: Introductionmentioning
confidence: 99%